Peran Lembaga Kebijakan Pengadaan Barang/Jasa Pemerintah (LKPP) Dalam Monitoring Dan Evaluasi Pengadaan Barang/Jasa Pemerintah - Widi Mulyadi; Nur Fitri Rahmawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
There is a high demand from the community for the government's performance in implementing the procurement of goods/services in an efficient, effective, transparent and accountable manner. Therefore, the implementation of government procurement of goods/services is required to avoid nepotism and corruption. The PBJ process within government agencies is a strategic activity in an effort to provide services to the community or business actors to increase the use of domestic production.Auctions for the procurement of goods/services are carried out by the government and private parties. Where the government PBJ auction is financed by the APBN, Provincial APBD, and Regency/City APBD, either by self-management or electronic auction, and the Auction for the Procurement of Goods/Services is carried out by the government, all of which are regulated in Presidential Regulation number 54 of 2010.In realizing an organizational goal, good management is needed, the management of management functions, one of which is the supervisory function, by top management is very decisive in achieving the planned organizational goals. Supervision is one of the efforts to strengthen control, including those carried out by the Central Government and Regional Governments, to avoid irregularities, irregularities, and leakages that will greatly harm local governments in carrying out their functions.